Development of a Full Mission Simulator for Pilot Training of Fighter Aircraft - BP, Shashidhara; Sekaran, Chandra; Bhatia, Yashpal; Kumar, Magesh; Kumar, Binesh; Kumar, Hemanth (Defence Science Journal, 2018)
With aircraft becoming more complex and avionics intensive and flight being almost autonomous based on waypoint navigation, software and displays becoming a significant component of the all glass cockpit of the modern day fighter aircraft, it is imperative that pilots are trained on missions using ground based full mission simulator (FMS) for routine flight as well as advanced missions. A flight simulator is as good as the real system only when it is able to mimic the physical system, both in terms of dynamics and layout so that the pilot gets the complete feel of the environment as encountered during actual sortie. The objective of this research paper is to provide a detailed insight into the various aspects of development of a FMS for pilot training with minimal maintenance operations for long hours of realistic flight training on ground. The approach followed by ADE in developing a FMS using a healthy mix of conventional flight simulation methodologies and novel approaches for various simulator sub-systems to tailor and meet the specific training needs, one presented. The FMS developed by ADE is presently being used by Indian Air Force for flight and mission critical training of squadron pilots.